2013
DOI: 10.1103/physreve.88.062507
|View full text |Cite
|
Sign up to set email alerts
|

Rotational and translational diffusion of anisotropic gold nanoparticles in liquid crystals controlled by varying surface anchoring

Abstract: We study translational and rotational diffusion of anisotropic gold nanoparticles (NPs) dispersed in the bulk of a nematic liquid crystal fluid host. Experimental data reveal strong anisotropy of translational diffusion with respect to the uniform far-field director, which is dependent on shape and surface functionalization of colloids as well as on their ground-state alignment. For example, elongated NPs aligned parallel to the far-field director translationally diffuse more rapidly along the director whereas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 66 publications
1
44
0
Order By: Relevance
“…The random sharp edges of NB particles allow them to efficiently localize the electromagnetic field and thereby provide high field enhancement for the incident electromagnetic wave [Fig 2(b)]. When dispersed in LCs, the NB particles possessed homeotropic anchoring of LC molecules at their surfaces, which led to quadrupolar elastic distortions 12,13 of director field n(r) with a half-integer disclination around particle's perimeter (inset in Fig. 1).…”
Section: B Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The random sharp edges of NB particles allow them to efficiently localize the electromagnetic field and thereby provide high field enhancement for the incident electromagnetic wave [Fig 2(b)]. When dispersed in LCs, the NB particles possessed homeotropic anchoring of LC molecules at their surfaces, which led to quadrupolar elastic distortions 12,13 of director field n(r) with a half-integer disclination around particle's perimeter (inset in Fig. 1).…”
Section: B Sample Preparationmentioning
confidence: 99%
“…3 Short (20×40nm) gold nanorods (SR) with capping ligands polystyrene (PS) or methoxy poly(ethylene glycol) thiol (mPEG) and disc-shaped gold nanoparticles with sharp irregular edges called 'Nanobursts' (NB) 12,13 were obtained from Nanopartz Inc. The relatively poly-disperse NSOL-functionalized gold NB nanoparticles had average lateral size ~ 500 nm, as indicated by the TEM images shown in Fig 2(a).…”
Section: B Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Two- [7][8][9][10][11] and three-dimensional 14 crystals were designed in nematics using different elastic dipoles and quadrupoles, and singular defects were tailored using spherical 16 and topologically non-trivial 17 colloidal particles. Recent studies also showed the importance of size [18][19][20][21][22][23][24] and shape [24][25][26][27][28][29][30][31] in elastic interactions and ensuing assemblies of colloidal particles in nematics. On the other hand, colloidal dispersions in twisted nematic and cholesteric LCs (CLCs) have received less attention [32][33][34][35][36][37][38][39][40][41][42][43]<...>…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in a suspended liquid with viscosity η s , and in a highly-diluted regime, the particles are able both to rotate freely without interacting each other due to the large distance and to diffuse due to the Brownian forces only (~ K B T ). The Brownian rotational and translation diffusion coefficients are defined as D r,B and D t,B ; for nearly spherical particles of diameter d , given by: Dr,B=kBT(πηsd3) Dt,B=kBT(6πηsR) while for a rod-like particle of length L and diameter d , and if the aspect ratio L / d is in the range 2 < L / d < 30, they are given by [36,37]: Dr,B=3kBT(ln(2Ld)0.8)(πηsL3) Dt,B=3kBT(ln(2Ld)0.8)(3πηsL) (with k B being the Boltzmann constant, and T the absolute temperature). The Equations (7a,b) and (8a,b) indicate the dependence of the diffusion on the geometrical radius and aspect ratio.…”
Section: Resultsmentioning
confidence: 99%